Humanisme, Keadilan, Dan Kesetaraan: Paralelitas Islam Dan Pancasila - Fithriati, Maryam (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2024)
Throughout the history of the Republic of Indonesia, religion and Pancasila have often faced an adversarial relationship. In fact, in much of the political history literature, the founding fathers of nationalism were often divided into those who proposed religion as the basis of the state (Islamic groups) and those who proposed the principles of secular nationalism as an alternative (nationalist groups). This reproduced polarity has led to suspicions about the incompatibility of values between Islam and Pancasila. Instead of reproducing the polarity, this article focuses on investigating the alignment of values and humanitarian spirit between Islam and Pancasila. This focus on the alignment of the values of humanism, justice and equality is expected to strengthen the basis of nationalism based on the spiritual capital of Indonesian society